Penerapan Model Integratif Learning untuk Meningkatkan Hasil Belajar Menulis dan Bercerita Rangkum Buku Nonfiksi - Murakip Murakip (Kelasa, 2019)
The results of a preliminary study of writing and telling the result of summary nonfiction books of a low so the reseascher need to solve the problem using the learning integrative model. The purpose of this study is to describe the application of the Integrative Learning Model to improve learning outcomes of writing a summary, and to tell the results of a nonfiction book summary.The research method developed was Classroom Action Research, Kemmis and Taggart models. The results showed that the results of writing a summary in the form of a series of main ideas in the content of non-fiction books, 21 students completed (65.63%) cycle I, 28 students completed (87.50%) cycle II, and told the results of the summary in the form of a series main ideas of the contents of the nonfiction book made, 20 students completed (62.50%) cycle I, 29 students completed (90.63%) cycle II. The results of the study prove that the application of the Integrative Learning Model can improve the assessment of learning outcomes of writing a summary and retelling the results of a nonfiction book summary for students of class VII-B of SMP Negeri 3 Pamekasan. AbstrakHasil studi pendahuluan menulis dan bercerita hasil rangkuman buku nonfiksi rendah sehingga peneliti perlu memecahkan masalah dengan menggunakan model Integratif Learning. Tujuan penelitian ini adalah mendeskripsikan penerapan Model Integratif Learninguntuk meningkatkan hasil belajar menulis rangkuman, dan bercerita hasil rangkuman buku nonfiksi.Metode penelitian yang dikembangkan adalahPenelitian Tindakan Kelas, model Kemmis dan Taggart.Hasil penelitian menunjukkan bahwa hasil menulis rangkuman dalam bentuk rangkaian gagasan pokok isi buku nonfiksi, 21 peserta didik tuntas (65,63%) siklus I, 28 Peserta didik tuntas (87,50%) siklus II, dan menceritakan hasil rangkuman dalam bentuk rangkaian gagasan pokok isi buku nonfiksi yang dibuat, 20 peserta didik tuntas (62,50%) siklus I, 29 Peserta didik tuntas (90,63%) siklus II. Hasil penelitian membuktikan bahwa penerapan Model Integratif Learning dapat meningkatkan penilaian hasilbelajar menulis rangkuman dan menceritakan kembali hasil rangkuman buku nonfiksipada peserta didik kelas VII-B SMP Negeri 3 Pamekasan.